2012
DOI: 10.1002/ctpp.201210038
|View full text |Cite
|
Sign up to set email alerts
|

On Recent Massively Parallelized PIC Simulations of the SOL

Abstract: Recent results of massively parallel kinetic (PIC/MC) simulations of the tokamak scrape-off layer are discussed. It is demonstrated that a number of well studied properties of the low-recycling divertor plasma, such as the sound speed and the average energy of plasma particles impinging on the divertors, cannot be generalized to the high recycling case. A new analytical model for plasma boundary condition has been derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…This indicates that three-dimensional fluid simulations with non-local parallel transport will be practicable. For comparison, [25] concluded that three-dimensional PIC simulations are beyond the reach of current or near-future supercomputers, as they would require ≥ 3 × 10 6 teraflops to run in one week. Indeed, even in one dimension, a single run of the BIT1 PIC code takes upwards of 12 hours on 512 processors [25], which would make it challenging even to use the PIC code just for parallel kinetic corrections in a three-dimensional fluid model, with many thousands of field lines.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that three-dimensional fluid simulations with non-local parallel transport will be practicable. For comparison, [25] concluded that three-dimensional PIC simulations are beyond the reach of current or near-future supercomputers, as they would require ≥ 3 × 10 6 teraflops to run in one week. Indeed, even in one dimension, a single run of the BIT1 PIC code takes upwards of 12 hours on 512 processors [25], which would make it challenging even to use the PIC code just for parallel kinetic corrections in a three-dimensional fluid model, with many thousands of field lines.…”
Section: Methodsmentioning
confidence: 99%
“…The forces acting on W as well as plasma parameters in front of divertor plates strongly depend on the velocity distribution functions (VDF) of the electrons and the main ions at the plasma boundary [15]. To obtain particle VDF in the divertor plasma selfconsistently we consider a slab model of the entire SOL bounded between the two divertor plates, separatrix and outer wall.…”
Section: Description Of the Sol Modelmentioning
confidence: 99%
“…While fully three-dimensional turbulent kinetic simulations of plasma turbulence using fully kinetic codes are nowadays out of reach, present models, now run on massively parallel computers, are able to describe the interaction of multiple ion species plasmas with a large number of neutral species, impurities, and also with the plasma facing components. The most advanced codes are able to describe tens of elastic, charge-exchange, excitation, ionization and charge-exchange collision processes (Tskhakaya 2012). …”
Section: Kinetic Description Of the Sol Dynamicsmentioning
confidence: 99%